KEANEKARAGAMAN JENIS PENYUSUN HUTAN DI KAWASAN ARBORETUM SYLVA UNIVERSITAS TANJUNGPURA PONTIANAK - Susilawati, .; Fahrizal, M; Manurung, Togar Fernando (Universitas Tanjungpura, 2017)
This research aims to determine a diversity of plants seedlings, saplings, poles, trees and to find out the the most dominant vegetation species as a composition in the area of Arboretum Sylva Â Tanjungpura University Pontianak. The method used is a survey method. Sampling was done by using the technique of random transect. The data were then analyzed descriptively and qualitatively, using the formula of Shannon Diversity Index. The results of this research showed that in the area of Arboretum Sylva Â Tanjungpura University Pontianak there are 15 species in the seedling stage, 35 species in the pole stage, 28 species in the sapling stage and 54 species in the tree stage. Species diversity index (H) on the growth rate showed a stable community with a diversity of species for seedlings with H value of 0.99496, for saplings with H value of 1.36105, for poles with H value of 1.25300 and for trees with H value of 1.31710. Dominance Index value (C) showed a species dominance rate that is in the low range because for the seedling stage, the C value was 0.13317; for sapling stage, the C value was 0.06231; for pole stage, the C value was 0.08404; for tree stage, the C value was 0, 1046. The species abundance index value (e) indicated the level of diversity is high because for the seedling stage, the e value was 0.84598, for the sapling stage, the e value was 0.88147, for the pole stage, the e value was 0.86584, for the tree stage, the e was 0,76028.Keywords: Arboretum, Diversity of forest composition, Pontianak.